2002
DOI: 10.1267/ahc.35.395
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Estrogen Receptor (ER) .ALPHA. and .BETA. in the Female Reproductive Tissues of Mice Neonatally Exposed to Diethylstilbestrol.

Abstract: Ontogenical expression of estrogen receptor (ER) isoforms, ERa and ERb, was examined in order to study the roles of the isoforms in the morphogenesis of neonatal diethylstilbestrol (DES) treatment in the female reproductive tissues using an immunohistochemical method. The intensity of ERa immunostaining gradually increased with aging in the epithelial cells of oviducts, uteri, cervices and vaginae in the vehicle-treated control animals. Neonatal DES-treatment up-regulated the expression of ERa in the epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…Several investigators have reported similar results in the uterus of mice exposed to DES perinatally [29][30][31][32]. By contrast, no ERβ protein was detected in the uterus of either controls or DES mice during maturation, and only the granulosa cells of the ovaries showed a positive reaction in both the control and DES-mice [15].…”
Section: ) Erα and Erβ Expressionsupporting
confidence: 53%
See 3 more Smart Citations
“…Several investigators have reported similar results in the uterus of mice exposed to DES perinatally [29][30][31][32]. By contrast, no ERβ protein was detected in the uterus of either controls or DES mice during maturation, and only the granulosa cells of the ovaries showed a positive reaction in both the control and DES-mice [15].…”
Section: ) Erα and Erβ Expressionsupporting
confidence: 53%
“…Until at least 15 days of age, DES-treatment strongly up-regulated expression of ERα in the epithelial cells in the genital tract including uteri, and down-regulated the expression in the stromal cells ( Fig. 1B) [15]. In the DES-mice even on day 4, almost all uterine epithelial cells exhibited strong ERα-immuoreaction ( Fig.…”
Section: ) Erα and Erβ Expressionmentioning
confidence: 86%
See 2 more Smart Citations
“…Frozen sections (7 m thick) were fixed with 4% paraformaldehyde dissolved in 0.15 M phosphate buffer (pH 7.4) for 20 min at room temperature (Yamashita, 2002). The fixed sections were washed with phosphate-buffered saline (PBS), 10 mM phosphate buffer, and pH 7.4 containing 0.85% NaCl, and were then treated with 0.2% glycine in PBS for 30 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%